PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MEDIA PEMBELAJARAN GAME INTERAKTIF WORDWALL PADA SISWA KELAS IV DI SD NEGERI 007 SUNGAI PINANG SAMARINDA - Listya Arum Juanti; Iksam; Rosita Putri Rahmi Haerani; Mustamiroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Studentd of SDN 007 Sungai Pinang in grade IV showed poor learning outcomes in Pancasila education subjects, especially about social and cultural diversity materials, which encouraged this research. The purpose of this study is to improve student learning outcomes through the use of learning media in the form of interactive wordwall games. This research is a class action research (PTK) which is carried out in two cycles, with each cycle consisting of two meetings. Each cycle goes through several stages, namely, planning, implementation, observation and reflection. The research subjects totaled 30 students, with a focus on improving learning outcomes using wordwall media. Observations, tests, and documentation are used to collect data. The results of the study show that the interactive game media wordwall has succeeded in improving student learning outcomes. The average score of students increased from 61,17 in the pre cycle with a completion percentage of the 30%, to 68 in the first cycle with a completion percentage of 50%, and to 78 in the second cycle with a completion percentage of 83,33%.